KONSEP KOMUNIKASI INTERPERSONAL DALAM MEMAHAMI KONFLIK KESETARAAN GENDER DI PSGA UIN JKT - Melsa Mendyana; Fahrus Sholeh; Nasichah Nasichah (IKIP Siliwangi, 2023)
The purpose of this study was to examine the relationship between interpersonal communication in understanding gender equality conflicts at PSGA UIN Jakarta. The subject of this study was the PSGA Team at UIN Jakarta with 4 lecturers from 4 Faculties involved. The data collection used was interviews which consisted of in-depth questions about PSGA UIN Jakarta. The data collection process was carried out using the method of visiting directly to the gender and children study room, participating in various activities carried out by the PSGA. The results of the study show that qualitatively the PSGA team always tries to make activities for students in preventing sexual violence and making a flow of handling, and handling it until it's finished, to form an anti-sexual violence task force. The biggest obstacle is that students are afraid to talk and complain about it to PSGA.Keywords: Gender Equality, Sexual Violence, PSGA